(untitled) (Physical Education, Health and Social Sciences, 2026)
Background: key stage in medical education, the move from preclinical to clinical training is frequently accompanied with substantial emotional, intellectual, and professional difficulties.It is crucial to comprehend students lived experiences throughout this stage in order to enhance clinical training and support networks. Methods: Sixteen medical students who had just finished their first clinical rotation participated in a qualitative phenomenology study.Purposive sampling was used to choose the participants.A structured questionnaire including demographic data, semistructured interview questions, and a quick experience rating scale were used to gather the data.The interviews lasted between twenty and thirty minutes and were held in a private environment.The sixstep thematic analysis method developed by Braun and Clarke was used to examine the data. Results: The research revealed seven major themes: emotional experiences, the difference between expectations and reality, transition difficulties, learning environments, patient contact and confidence building, professional identity creation, and coping and support networks. During the first part of their clinical exposure, students reported feeling excited, afraid, and anxious. Expectations and actual clinical experiences were shown to differ significantly, with students experiencing busier and less structured settings than they had anticipated. It was thought to be difficult to move from academic understanding to real-world implementation. Both supportive and unsupportive interactions were noted in the diverse learning environment. Increased self-assurance and skill improvement were greatly aided by patient encounters. Students also started to form a feeling of professional identity. Support from family and peers appeared as crucial coping strategies. Conclusion: Medical students’ emotional adaption, self-assurance, and professional identity are all significantly shaped by their first clinical rotation, which is a life-changing event. Improving supportive learning settings and closing the theory-practice gap could make the transition to clinical training easier and enhance overall academic results.